Comparative Analysis and Optimization of Stray Dog Rescue Policy - Wang, Xingye (International Journal of Social Sciences and Public Administration, 2025)
This study aims to thoroughly analyze the stray dog rescue policies to address the numerous challenges posed by the current stray dog issue. By systematically reviewing relevant global policies and employing literature review, case analysis, and comparative research methods, this study conducts a comprehensive and in-depth analysis of stray dog rescue policies. The research reveals that foreign policies demonstrate significant advantages in animal welfare protection and adoption incentives, but face shortcomings such as high capital consumption. While China’s policies have certain provisions regarding capture and sheltering, they encounter issues including incomplete legal frameworks and low public participation. Based on these findings, it is recommended to improve the legal system, broaden funding channels, strengthen public education and interdepartmental coordination to optimize and effectively implement stray dog rescue policies. This will address the stray dog problem and achieve an organic balance between public health, social security, and animal welfare.